The Influence of Store Atmosphere and Location on Purchasing Decisions at Tuanjana Coffee Shop, Bandar Lampung - Setyawan, Sabrina; Rinova, Dora (Journal of Environmental Economics and Sustainability, 2025)
This research examines the effect of Store Atmosphere and Location on purchasing decisions at Tuanjana Coffee Shop in Bandar Lampung. The study adopts a quantitative approach with a descriptive method. 92 respondents were selected as the sample, and the data were analyzed using multiple linear regression analysis. The t-test results reveal that the Store Atmosphere variable significantly influences purchasing decisions at Tuanjana Coffee Shop in Bandar Lampung. Furthermore, the Location variable also significantly affects purchasing decisions at the coffee shop. Based on the coefficient of determination test, the R square value of 0.761 indicates that Store Atmosphere and Location collectively account for 76.1% of the variance in purchasing decisions. The remaining 23.9% is attributed to other factors not covered in this study.